Olhares de professoras sobre as relações étnico-raciais em suas trajetórias formativas - Crispam, Josiane Ramos Ilha (2024)
This research is linked to the Curso de Mestrado Profissional, do Programa de Pós Graduação em Políticas Públicas e Gestão Educacional, na LP2 - Linha de Pesquisa Gestão Pedagógica e Contextos Educativos. It is also included in the activities developed by the Research Group TRAVESSIAS: Cotidiano, Infância e Docência, more specifically in its Umbrella Project COTIDIANO E INFÂNCIA: Desafios e possibilidades para se pensar a Gestão Pedagógica, a Educação das crianças e a Formação de professores. Its main theme is ethnic-racial relations and the views of educators regarding the self-identification of their school community. The general objective of this study is to ““Identify and analyze the perceptions of teachers regarding issues related to the identity and self-identification of black children and the school community”.”. As specific objectives, we list: to verify the perceptions of early childhood educators regarding the identity and self-identification of black children and the school community; to raise awareness of the importance of building a positive identity for black children, and to highlight possible actions to consolidate the proposal of being an anti-racist school. The main authors studied were: Cavalheiro (2001; 2023), Gomes (2002; 2008; 2023), Kaercher (2005; 2021), Lima (2011; 2020), Macedo (2021), Munanga (1986; 2004; 2020), Nóvoa (2002), Pinheiro (2023), Quadros (2023), Silva (2012), Sodré (1999) and Souza (2021). The methodological approach adopted is qualitative, which sought, through a Case Study, to respond to the concerns regarding the chosen theme. As a methodological approach to data collection, four meetings called “Conversation Circles” were held with teachers from Escola Pardais. As a summary of the meetings, participants were invited to write letters to the researcher. The letters addressed the self-identification, educational path, and pedagogical practices of each participant. As the final product of this study, we present a letter written collectively by the group involved, addressed to new teachers who will join the school community, so that they may learn about the school‟s anti-racist identity and develop pedagogical practices that aim to educate for ethnic-racial relations.